Genetic analysis of Rhipicephalus sanguineus sensu lato ticks parasites of dogs in Africa north of the Sahara based on mitochondrial DNA sequences - Chitimia-Dobler, Lidia; Langguth, Johanna; Pfeffer, Martin; Kattner, Simone; Küpper, Thomas; Friese, Daniela; Guglielmone, Alberto; Nava, Santiago (2017)
The aim of this work was to determine the evolutionary relationship among tick populations of Rhipicephalus sanguineus sensu lato distributed in Africa north of the Sahara and different lineages of R. sanguineus s.l. distributed in different regions of Sub-Saharan Africa, America and Europe through the analysis of DNA sequences of two mitochondrial genes. One hundred and thirty six 16S rRNA gene sequences and twenty-seven 12S rRNA gene sequences of R. sanguineus s.l. were analyzed. Phylogenetic analyses were performed including different lineages of R. sanguineus s.l. from America, Europe and Africa, and species belonging to the R. sanguineus group as Rhipicephalus camicasi, Rhipicephalus guilhoni, Rhipicephalus sulcatus, Rhipicephalus rossicus, Rhipicephalus pusillus, Rhipicephalus turanicus and Rhipicephalus leporis. At least two different lineages of R. sanguineus s.l. are living in sympatry in Africa north of the Sahara. One of these mitochondrial lineages belongs to the same evolutionary entity that R. sanguineus s.l. from tropical areas of America, R. sanguineus s.l. from Sub-Saharan Africa, R. camicasi and R. guilhoni. The other mitochondrial lineage of R. sanguineus s.l. present in Africa north of the Sahara is phylogenetically associated to R. sanguineus s.l. ticks from southeastern Europe (Romania, Turkey and Greece). Both evolutionary entities are clearly different to the evolutionary entity formed by R. sanguineus s.l. from western Europe and temperate areas of America. Thus, the name R. sanguineus s.s. cannot be assigned to any of the two evolutionary entities present in Africa north of the Sahara. The taxonomic status of these taxa will remain unresolved until new lines of evidence become available to complement the current results based on mitochondrial DNA.